STUDI PERBANDINGAN MORALITAS MENGGUNAKAN MODEL TC DAN NHT DENGAN MEMPERHATIKAN KONSEP DIRI - Astika Kusni Wendhari; Edy Purnomo; Yon Rizal (FKIP Unila, 2015)
The problem of this research was low morality of students in the integrated social science subject at VIII grade students odd semester SMP Negeri 2 Pesawaran. The purpose of this research is to investigate the difference of morality and interaction of TC model students and NHT students regarding on the self-concept. The method used comperative with experiment approach. The result of analysis showed: (1) there is a difference of students morality in integrated social science learning between the student with TC and NHT model, (2) morality of students in integrated social science learning, TC model is higher than NHT on the positive self-concept student, (3) morality of students in integrated social science learning, TC is lower than NHT on the negative self-concept students (4) there is an influence of interaction between the models with self-concept on integrated social science learning and, (5) there is a difference in the average of morality between students who have positive self-concept and negative self- concept.Masalah penelitian ini adalah rendahnya moralitas siswa pada pelajaran IPS Terpadu siswa kelas VIII semester ganjil SMP Negeri 2 Pesawaran. Tujuan penelitian ini adalah mengetahui perbedaan moralitas dan interaksi siswa model TC dan NHT dengan memperhatikan konsep diri. Metode yang digunakan komparatif dengan pendekatan eksperimen. Hasil analisis:(1) ada perbedaan moralitas siswa dalam pembelajaran IPS Terpadu antara siswa dengan model TC dan NHT, (2) moralitas siswa dalam pembelajaran IPS Terpadu dimana model TC lebih tinggi dibandingkan dengan NHT pada konsep diri siswa yang positif, (3) moralitas siswa dalam pembelajaran IPS Terpadu dimana TC lebih rendah dibandingkan NHT pada konsep diri siswa negatif, (4) ada pengaruh interaksi antara model dengan konsep diri pada pembelajaran IPS Terpadu dan, (5) Ada perbedaan rata-rata hasil moralitas antara siswa yang memiliki konsep diri positif dan konsep diri negatif.Kata kunci: konsep diri, moralitas, NHT, TC